Flash vocal-Assisted Instruction: An Experimental Study on Students’ Writing Skills - Putri Ramadhani M (CV. Arunika Media Nusantara, 2025)
This study aims to determine the effectiveness of using Flashvocal learning media in improving students' writing skills and their interest in learning to write English. Flashvocal is an interactive learning media that combines visual, audio, and written text elements that aim to improve students' language skills, especially in composing descriptive texts. The research method used is a quantitative method with a quasi-experimental approach involving two classes of eighth grade students at SMPN 1 Tinambung. One class as an experimental class uses Flashvocal in learning, while the control class is taught using conventional methods. Data were collected through pre-test, post-test, and questionnaires to determine changes in students' writing skills and learning interests. The results of data analysis showed that although there was an increase in the average post-test score in the experimental class from 9.68 to 11.84, the results of the Independent Samples T-Test showed a significance value (2-tailed) of 0.436, greater than 0.05. This indicates that there is no statistically significant difference between the experimental class and the control class in terms of improving writing skills. However, based on descriptive analysis and student responses through questionnaires, the use of Flashvocal showed a positive influence in improving writing organization, idea development, and student motivation in writing. Thus, Flashvocal has practical potential in increasing student engagement and enriching the writing learning process in the classroom.